Analysis on The Mental Workload of Female Lecturers During The Covid-19 Pandemic - Euis Nina Saparina Yuliani; Sri Suhartini; Daisy Ade Riany; Defi Norita; Hernadewita Hernadewita; Emi Pahiba (Universitas Mercu Buana, 2022)
The coronavirus (Covid-19) pandemic continues to create significant effect than initially predicted. In addition, the virus spread showed rapid increment, since March 2020, leading to several impacts on human lives, e.g., education. Furthermore, various government policies, including social distance greatly influences teaching and learning activities, both in high schools and universities. As a consequence, conventional face-to-face learning model was temporarily suspended. This implies the need to engage online education. Prior to the outbreak, the mental workload of lecturers was relatively intense, comprising the three basic pillars of higher education (Tridharma), termed education, research and community service, as well as other additional tasks, including final year project supervisions and hold structural position. During the pandemic, mental workload considerably increased considerably as most lecturers, particularly the females also served as home teachers. Therefore the purpose of this research is to analyze the mental workload of female lecturers during the Covid-19 pandemic in Indonesia. Questionaire is used to measure mental workload taken from the National Aeronautics and Space Administration-Task-Load Index (NASA-TLX). Furthermore, the survey is applied to evaluate job demands. The results showed that teaching, research and housewive role influence the mental workload as an aspect with the maximum score. In comparison, a maximum score of 29% on the mental demand aspect generates a physical demand aspect of 27%.